How can mental health and faith-based practitioners work together? A case study of collaborative mental health in Gujarat, India. (June 2016) - Shields, Laura; Chauhan, Ajay; Bakre, Ravindra; Hamlai, Milesh; Lynch, Durwin; Bunders, Joske
Despite the knowledge that people with mental illness often seek care from multiple healing systems, there is limited collaboration between these systems. Greater collaboration with existing community resources could narrow the treatment gap and reduce fragmentation by encouraging more integrated care. This paper explores the origins, use, and outcomes of a collaborative programme between faith-based and allopathic mental health practitioners in India. We conducted 16 interviews with key stakeholders and examined demographic and clinical characteristics of the user population. Consistent with previous research, we found that collaboration is challenging and requires trust, rapport-building, and open dialogue. The collaboration reached a sizeable population, was reviewed favourably by key stakeholders—particularly on health improvement and livelihood restoration—and perhaps most importantly, views the client holistically, allowing for both belief systems to play a shared role in care and recovery. Results support the idea that, despite differing practices, collaboration between faith-based and allopathic mental health practitioners can be achieved and can benefit clients with otherwise limited access to mental health care.